Analisis Faktor-Faktor Keterlambatan Mahasiswa Tingkat Akhir Di Program Studi Pendidikan Ekonomi FKIP ULM Dalam Menyelesaikan Skripsi - Saputra, Made; Ratumbuysang, Monry Fraick Nicky Gillian; Rahmattullah, Muhammad; Hasanah, Mahmudah (Universitas Negeri Surabaya, 2024)
This research aims to determine the factors inhibiting the completion of a thesis in the FKIP ULM economics education study program in the 2016-2019 class. This research uses quantitative research with descriptive quantitative research, using a questionnaire which will be distributed using a Likert Scale with a sample size of 92 participants. With the validity research instrument test used in this research, the validity test itself uses the Product Moment (Pearson) correlation statistical calculation formula. And testing the reliability test was measured using the Cronbach'Alpha method. The data analysis technique used was Descriptive Analysis. Based on research that has been carried out, it is stated that the factors of delay in completing the thesis affect the graduation rate of FKIP ULM economic education students. is in the very high category with a percentage of 97.9%. The factors that cause delays in completing a student's thesis are internal factors and external factors consisting of internal factors, namely motivation, intelligence, health, attitudes and study habits, psychology. External factors consist of family factors, availability of learning resources, peer environment, lecturers, and other factors.